Driving Under the Influence of Cannabis: A Framework for Future Policy. (June 2019) - Chow, Robert M.; Marascalchi, Bryan; Abrams, Winfred B.; Peiris, Nathalie A.; Odonkor, Charles A.; Cohen, Steven P.
Abstract : Marijuana is the most widely consumed illicit substance in the United States, and an increasing number of states have legalized it for both medicinal and recreational purposes. As it becomes more readily available, there will be a concurrent rise in the number of users and, consequently, the number of motor vehicle operators driving under the influence. This article examines the cognitive and psychomotor effects of cannabis, as well as current policy concerning driving under the influence of drugs. The authors performed a MEDLINE search on the epidemiology of cannabis use, its cognitive and psychomotor effects, and policies regarding driving under the influence of drugs. Twenty-eight epidemiological studies, 16 acute cognitive and psychomotor studies, 8 chronic cognitive and psychomotor studies, and pertinent state and federal laws and policies were reviewed. These search results revealed that marijuana use is associated with significant cognitive and psychomotor effects. In addition, the legalization of marijuana varies from state to state, as do the laws pertaining to driving under the influence of drugs. Marijuana is a commonly found illicit substance in motor vehicle operators driving under the influence of drugs. Current evidence shows that blood levels of tetrahydrocannabinol do not correlate well with the level of impairment. In addition, although acute infrequent use of cannabis typically leads to cognitive and psychomotor impairment, this is not consistently the case for chronic heavy use. To establish the framework for driving under the influence of cannabis policy, we must review the current published evidence and examine existing policy at state and federal levels.